Phenomenological study: parenting experiences by mothers of domestic violence victims - Indah Rizky Valiant; Elsye Maria Rosa (Alma Ata University Press, 2022)
Background: Domestic violence (DV) is a health problem that often occurs in women in the community. Violence that is often experienced by women is physical violence, psychological violence and sexual violence. Domestic violence has a negative impact on women, namely a decrease in health status and mental disorders. Women who are victims of domestic violence who have mental health problems are at risk of causing child rearing disorders. Objectives: The purpose of this study was to explore the experience of parenting by mothers of domestic violence victims. Methods: This study uses a qualitative method with a phenomenological approach. The data collection process was carried out using a semi-structured interview method. The sampling technique used snowball sampling. The characteristics of the participants in this study were women who were victims of domestic violence who had children who were still married or divorced. The participants in this study were 7 women victims of domestic violence who had children. The data analysis used is thematic analysis using Nvivo 12 software. Results: There are 4 main themes in this study. The themes raised were causes of domestic violence (financial quarrel and cheating husband), the role of parenting by mothers of domestic violence victims, fulfilling the psychological needs of children by mothers of domestic violence victims, and the application of rules and punishments for children by mothers of domestic violence victims. Conclusions: This study concludes that mothers who are victims of domestic violence continue to provide positive parenting for their children by taking care of their children, meeting their needs and guiding their children. Health services need to develop a screening program for victims of domestic violence to detect cases of domestic violence in the community. Programs for developing parenting patterns or good parent-child relationships also need to be carried out, especially for families at risk or experiencing domestic violence so that mothers of domestic violence victims continue to provide positive parenting for their children.